2012
DOI: 10.1051/matecconf/20120202009
|View full text |Cite
|
Sign up to set email alerts
|

Effet de la combinaison de la chaux et de la pouzzolane naturelle sur le compactage et la résistance des sols mous argileux

Abstract: Abstract. Soft soil stabilization has been practiced for quite some time by mixing additives, such as cement, lime and fly ash to the soil to increase its strength. However, there is a lack of investigations on the use of natural pozzolana alone or combined with lime for ground improvement applications. An experimental program was undertaken to study the effect of using lime, natural pozzolana or a combination of both on the geotechnical characteristics of soft soils. Lime or natural pozzolana was added to sof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 9 publications
3
4
0
1
Order By: Relevance
“…This observation is in good agreement with the results in [6,[18][19][20]. Similar trends of the liquid limit have been observed by other researchers on materials treated with lime and pozzolan [9,21], and on materials treated with fly ash [22][23][24].…”
Section: A Effect Of the Cement On The Liquid Limitsupporting
confidence: 91%
See 4 more Smart Citations
“…This observation is in good agreement with the results in [6,[18][19][20]. Similar trends of the liquid limit have been observed by other researchers on materials treated with lime and pozzolan [9,21], and on materials treated with fly ash [22][23][24].…”
Section: A Effect Of the Cement On The Liquid Limitsupporting
confidence: 91%
“…The same trends have been observed on materials treated with lime [28] and on materials treated with limestone [5]. The same behavior was also observed in [9,22,[29][30]. It has been shown that the addition of fly ash at low calcium soil swelling causes an increase in the plasticity limit, this is due to the replacement of the fine particles by the larger particles [7,9].…”
Section: B Effect Of the Cement On The Plastic Limitsupporting
confidence: 78%
See 3 more Smart Citations